Aplikasi GIS untuk Perubahan Penggunaan Lahan di Kuta, Kuta Utara, dan Kota Denpasar, Provinsi Bali - Hernanda Putri Emmanuel Sari; I Wayan Diara; R. Suyarto (Fakultas Pertanian, Universitas Udayana, 2023)
The increase in population and tourism in Kuta, North Kuta and Denpasar City has led to an increase in the need for land which in turn will lead to changes in land use. This triggers a change in land use from agricultural land to non-agricultural land. This study aims to analyze changes in land use in Kuta, North Kuta and Denpasar City from 2000 to 2020. Land use is classified into 7 types of land use with a guided classification technique. The data used is in the form of spatial data from Landsat 7 imagery in 2000 and Landsat 8 imagery in 2010 and 2020. The research was conducted in November 2022-January 2023 in Denpasar City. Based on the results of the study, it showed that there were changes in land use in 2000-2020, such as a decrease in the area of paddy fields by 4,334.01 ha (56.7%) and an increase in the area of settlements by 5,043.51 ha (69.3%).